Thiết kế bộ điều khiển tự chỉnh thông số PID trên cơ sở hệ luật - Dũng, Lê Bá (Journal of Computer Science and Cybernetics, 2016)
An implementation of a selp-tunning PID Controller using Rule-besed fuzzy expert systems approached is described in this paper. The algorithm uses fuzzy logic inferencing to adaptivity tune the parameters of the PID Controller.